Definisi dan Jalur Penularan Severe Acute Respiratory Syndrome Coronavirus 2 atau COVID 19 - joko tri atmojo; Prima Soultoni Akbar; Saras Kuntari; Ika Yulianti; Aquanturi Tri Darmayanti (Jurnal Pendidikan Kesehatan, 2020)
Since it was first reported at the end of 2019 Severe Acute Respiratory Syndrome Coronavirus 2 or SARS CoV 2 or COVID 19 has infected more than 2 million people in just under 5 months worldwide. Based on the above data the author will make a review and explain the definitions and also various routes of transmission of infection based on evidence that has been published and summarized. The review was carried out in April 2020, by searching the article through an online database and keywords Review AND COVID 19 OR Severe Acute Respiratory Syndrome Coronavirus 2 AND Review OR Coronavirus Disease 2019 AND Review AND transmission route. SARS CoV 2 or COVID 19 is a virus of the type of beta coronavirus with a higher transmission rate than SAR CoV or MERS. The most active human to human transmission pathway is through close contact with droplets and aerosols, although the virus is still present in feces, tears and urine. But the potential for transmission still needs to be studied. The incubation period of the virus is 0 until 24 days with an average of the first symptoms until death is 3 until 14 days.